Frequency of Manuscript Publication Following Presentation of EMS Abstracts at National Meetings. Issue 3 (15th April 2014) - Clemency, Brian M.; Thompson, Jeffrey J.; Lindstrom, Heather A.; Gurien, Steven; Jaison, Berly A.; Grates-Sciarrino, Alexis A.
Abstract: Introduction: Specialized knowledge and a scientific body of literature are the foundation of the recognition of Emergency Medical Services (EMS) as a subspecialty within emergency medicine (EM). Emergency Medical Services research often is presented at national meetings and published in abstract form, but full publication occurs less frequently. Problem: The primary goal of the study was to determine the rate at which EMS-related research presented at selected conferences went on to manuscript publication. A secondary goal was the determination of the time to manuscript publication. Methods: A cross-sectional study of published abstracts from the 2003-2005 national meetings of the American College of Emergency Physicians (ACEP), Society for Academic Emergency Medicine (SAEM), National Association of EMS Physicians (NAEMSP), Association of Air Medical Services (AAMS), and the National Association of EMS Educators (NAEMSE) was conducted to identify EMS-related abstracts. PubMed (National Center for Biotechnology Information, Bethesda, Maryland USA) was searched using abstract title keywords and authors' names to determine if the study had been published in a PubMed-indexed journal in the time since presentation and abstract publication. Results: Abstracts for the five conferences were reviewed for 2003-2005. Six hundred and thirty-five EMS-related abstracts met the inclusion criteria. The total number of EMS abstracts presented and the percent subsequently published as a manuscript were: SAEM 135, 53.3%; ACEP 128, 48.4%; NAEMSP 282, 42.9%; AAMS 66, 33.3%; and NAEMSE 24, 16.7%. The overall rate of publication was 44.3%. The average time to publication was 22.2 months (SD = 16.5 months, range = 0-94 months). Conclusion: Less than half of EMS abstracts go on to manuscript publication. This may represent missed opportunities for the growth of EMS as a subspecialty. BM Clemency, JJ Thompson, HA Lindstrom, S Gurien, BA Jaison, AA Grates-Sciarrino .Frequency of manuscript publication following presentation of EMS abstracts at national meetings .Prehosp Disaster Med .2014 ;29 (3 ):1 -5 .